Fungsi Musik Talempong Bagi Masyarakat di Nagari Andiang Kecamatan Suliki Kabupaten Lima Puluh Kota Sumatera Barat - Aisyah Aisyah; Idawati Idawati (Journal of Creative Student Research, 2025)
The research entitled "The Function of Talempong Music for the Community in Nagari Andiang, Suliki District, Limapuluh Regency, West Sumatra City" aims to reveal in depth how Talempong Music functions in the life of the Community in Nagari Andiang. This research uses a Descriptive Analysis approach with Qualitative Methods and the theory of musical function proposed by Alan P. Merriam (1964). The location of this research was carried out in Nagari Andiang, Suliki District, Limapuluh Kota Regency, West Sumatra Province, involving 7 sources. Data was collected through interviews, observations and documentation that focused on the Talempong music group and the community in Nagari Andiang. The results of this research show that Talempong music has various functions, including; 1) Function as emotional expression, 2) Function as a medium of entertainment, 3) Function as physical reaction, 4) Function as validation of social institutions, 5) Function as cultural preservation, 6) and Function as integration of society in randai performances.